Current condition of Bathypogon types (Diptera: Asilidae) described by Frank M. Hull and housed in the South Australian Museum of Natural History with notes on other Bathypogon types - Lavigne, Robert J. (Zootaxa, 2020)
The current condition of the types of Bathypogon, described by Frank M. Hull 1956–1959, are listed. By his own admission, a portion of the material borrowed from the South Australian Museum was destroyed by “pests”. Note is made that the holotype of Bathypogon microdonturus is missing and presumed destroyed. Additions are made to the published data based on data on the Type specimen labels. Photos of the hypandrium of some Bathypogon holotypes that reside in the SA Museum collection are provided.